Analisis Sentimen Twitter dan Pengaruhnya Kepada Masyarakat Terhadap Jatuhnya Cryptocurrency - Oktasia Nasution, Hafiza; Noviasari, Henni; Nasution, Salhazan; Melinda, Lisa (IT Journal Research and Development, 2022)
Cryptocurrency has become a global phenomenon nowadays. Based on the results of the GlobalWebIndex Survey, around 10% of internet users in Indonesia have digital currencies. But in recent years, the price of the cryptocurrency has fallen. It has resulted in people starting to hesitate to invest in crypto. This problem causes responses from the community, such as positive, negative, and neutral responses. This study aims to classify public opinion through the response to the fall of crypto by applying sentiment analysis through Twitter social media. Sentiment analysis data collection on Twitter uses the python programming language. There are three stages in the data analysis process: data crawling, preprocessing, and the results of classification and visualization. Based on research from sentiment analysis through social media Twitter, it was obtained that 57.9% produced a neutral value, 35.7% produced a positive value, and 6.4% produced a negative value.